The bright long-lived Type II SN 2021irp powered by aspherical circumstellar material interaction I. Revealing the energy source with photometry and spectroscopy - Reynolds, Thomas M.; Nagao, Takashi; Gottumukkala, Rashmi; Gutierrez, Claudia P.; Kangas, Tuomas; Kravtsov, Timo; Kuncarayakti, Hanindyo; Maeda, Keiichi; Elias-Rosa, Nancy; Fraser, Morgan; Kotak, Rubina; Mattila, Seppo; et al. (EDP Sciences, 2026)
Context
Some core-collapse supernovae (CCSNe) are too luminous and radiate too much total energy to be powered by the release of thermal energy from the ejecta and radioactive-decay energy from the synthesised 56Ni/56Co. A source of additional power is the interaction between the supernova (SN) ejecta and the massive circumstellar material (CSM). This is an important power source in Type IIn SNe, which show narrow spectral lines arising from the unshocked CSM, but not all interacting SNe show such narrow lines.
Aims
We present photometric and spectroscopic observations of the hydrogen-rich SN 2021irp, which is both luminous, with Mo < −19.4 mag, and long-lived, remaining brighter than Mo = −18 mag for ∼250 d. We show that an additional energy source is required to power such a SN, and we determine the nature of the source. We also investigate the properties of the pre-existing and newly formed dust associated with the SN.
Methods
Photometric observations show that the luminosity of the SN is an order of magnitude higher than typical Type II SNe and persists for much longer. We detect an infrared excess attributed to dust emission. Spectra show multi-component line profiles, an Fe II pseudo-continuum, and a lack of absorption lines, all typical features of Type IIn SNe. We detect a narrow (< 85 kms−1) P Cygni profile associated with the unshocked CSM. An asymmetry in emission line profiles indicates dust formation occurring from 250–300 d. Analysis of the SN blackbody radius evolution indicates asymmetry in the shape of the emitting region.
Results
We identify the main power source of SN 2021irp as extensive interaction with a massive CSM, and that this CSM is distributed asymmetrically around the progenitor star. The infrared excess is explained with emission from newly formed dust although there is also some evidence of an IR echo from pre-existing dust at early times.